A perfect refractory electrical storm by acute toxicity of accidental aconitine intake - Francesca Menichetti (Emergency Care Journal, 2021)
A 51-years-old male presented with drooling, hematemesis and diarrhea in emergency department after accidental ingestion of homemade aconitine tincture. Examination revealed shock and initial ECG showed atrial fibrillation. The patient suddenly developed a pulseless wide QRS complex tachycardia requiring resuscitation maneuvers. The rhythm varied from monomorphic ventricular tachycardia to torsade de point to ventricular fibrillation. Repeated direct-current cardioversions were unsuccessful. After intravenous electrolyte correction and anti-arrhythmic drugs administration, a last direct-current shock was finally successful. Bradycardia and ventricular excitability persisted over 12 hours with gradual normalization. Patient was discharged in normal sinus rhythm without any medication and on follow-up he was totally asymptomatic.